Curing formula and curing method for cement containing strontium and cesium medium-low radioactive waste liquid

By adding graphene oxide to the cement cured medium of medium and low drain waste liquid, the pore structure and the adsorption capacity are improved, the problems of high porosity and limited nuclide blocking performance of silicate cement cured bodies are solved, and efficient curing of radionuclides in the waste liquid is achieved.

CN119912216APending Publication Date: 2025-05-02HUNAN CITY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510084397.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the silicate cement cured body is treated with horizontal radioactive waste liquid, there are problems such as high porosity and limited nuclide blocking performance, which leads to difficulties in safe handling and disposal of radioactive waste liquid.

Method used

Graphene oxide is used as an admixture to improve the pore structure of the cement cured body of medium and low-level waste liquid, reduce porosity, and improve the adsorption and solid solution capacity of the cured body to radionuclides.

Benefits of technology

By reducing porosity and improving adsorption capacity, the cement curing effect of the cement cured body on typical nuclides 90Sr and 137Cs in medium and low-level waste liquid is significantly improved, and efficient curing of medium and low-level waste liquid containing radionuclides is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912216A_ABST
    Figure CN119912216A_ABST
Patent Text Reader

Abstract

The invention discloses a cement curing formula containing strontium and cesium medium-low radioactive waste liquid, which comprises composite Portland cement, waste liquid, graphene oxide and an additive, and the mass percentages of the waste liquid, the graphene oxide and the additive in the cement are 45-65%, 0.03-0.07% and 0.12-0.42% respectively; the liquid-ash ratio is 0.55 to 0.65. The preparation method comprises the following steps: weighing the composite Portland cement, the waste liquid, the graphene oxide and the additive in proportion; the method comprises the following steps: mixing a graphene oxide solid, an additive and a part of waste liquid to prepare a graphene oxide suspension, and preparing a graphene oxide dispersion liquid by using a dispersion process; putting the rest waste liquid, the composite Portland cement and the graphene oxide dispersion liquid into a cement solidification barrel, and uniformly stirring to obtain cement paste; and pouring the cement paste into the prefabricated mold and curing. According to the invention, by adding the graphene oxide, high-efficiency solidification of the ordinary Portland cement on the low and medium level radioactive waste liquid containing radionuclides Cs and Sr is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of radioactive waste liquid solidification, and in particular relates to a cement solidification formula and a solidification method for medium and low-level waste liquid containing strontium and cesium. Background Art

[0002] Driven by the goals of carbon peak and carbon neutrality, China's energy system is accelerating its transformation towards a clean and low-carbon direction. As a low-carbon energy source, nuclear energy has become an important force in replacing fossil energy and promoting the transformation of energy structure due to its advantages such as no greenhouse gas emissions in the production process, low carbon emissions throughout its life cycle, high energy density and non-intermittent operation. However, during the back-end processing of the nuclear fuel cycle, a large amount of medium-level radioactive waste liquid containing typical nuclides such as 137Cs and 90Sr will be generated. Among them, 137Cs is one of the most difficult nuclides to solidify and easy to migrate through leaching due to its high mobility and half-life of 30.2 years.

[0003] In response to this challenge, cement solidification technology, as a common method for treating low- and intermediate-level radioactive liquid waste, is widely used in the solidification treatment of low- and intermediate-level radioactive liquid waste, evaporation residues, mud, waste resins and incineration ash due to its advantages of stable solidified body performance, simple process operation and high cost-effectiveness. This technology uses cement as the main inorganic gel solidification matrix and adds additives such as fly ash, attapulgite, mineral powder, zeolite, etc. to improve the performance of the cement solidified body and enhance the adsorption capacity of radionuclides. However, when treating intermediate-level radioactive liquid waste, silicate cement solidified bodies have problems such as high porosity and limited radionuclide blocking performance, which is a key problem in the safe treatment and disposal of radioactive liquid waste. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a strontium and cesium-containing low- and medium-level radioactive waste liquid cement solidification formula, which uses graphene oxide as an admixture to improve the pore structure of the low- and medium-level radioactive waste liquid cement solidification body, reduce the porosity, and improve the adsorption and solid solubility capacity of the solidification body for radioactive nuclides.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A cement curing formula for medium and low-level waste liquid containing strontium and cesium comprises composite silicate cement, waste liquid, graphene oxide and additives, wherein the waste liquid, graphene oxide and additives account for 45-65%, 0.03-0.07% and 0.12%-0.42% of the cement mass respectively; and the liquid-to-cement ratio is 0.55-0.65.

[0007] Furthermore, the composite silicate cement model is P.C42.5R, the graphene oxide is a high-purity single-layer graphene oxide solid, the additive is a polycarboxylic acid water reducer or a lignin sulfonate water reducer, and the effective ingredient content of the additive is ≥60%.

[0008] Furthermore, the four components of composite silicate cement, waste liquid, graphene oxide and polycarboxylate water reducer account for 60.48%, 39.31%, 0.04% and 0.16% of the cement mass, respectively, and the liquid-cement ratio is 0.65.

[0009] Furthermore, the mass percentages of composite silicate cement, waste liquid, graphene oxide and lignin sulfonate water reducer are 60.43%, 39.28%, 0.04% and 0.25%, respectively, and the liquid-cement ratio is 0.65.

[0010] Furthermore, the mass percentages of composite silicate cement, waste liquid, graphene oxide and polycarboxylate water reducer are 64.41%, 35.42%, 0.03% and 0.12%, respectively, and the liquid-cement ratio is 0.55.

[0011] Furthermore, the mass percentages of composite silicate cement, waste liquid, graphene oxide and lignin sulfonate water reducer are 64.37%, 35.40%, 0.03% and 0.19%, respectively, and the liquid-cement ratio is 0.55.

[0012] The present invention also provides a method for curing a low-level radioactive liquid waste cement curing formula containing strontium and cesium, comprising the following steps:

[0013] Step S1, weighing composite silicate cement, waste liquid, graphene oxide and additives according to a ratio;

[0014] Step S2, mixing graphene oxide solid, additives and part of the waste liquid to prepare a graphene oxide suspension with a concentration of 5 mg / ml, and preparing a graphene oxide dispersion by a dispersion process;

[0015] Step S3, putting the remaining waste liquid, composite silicate cement and the graphene oxide dispersion obtained in step S2 into a cement curing barrel, stirring evenly to obtain cement slurry;

[0016] Step S4: pour cement slurry into the prefabricated mold and cure it.

[0017] Furthermore, in step S4, the curing conditions are temperature T≈20±5°C and relative humidity RH≥90%.

[0018] The present invention utilizes the property of graphene oxide in enhancing the performance of cement-based materials and the adsorption property of graphene oxide on heavy metal ions to improve the pore structure of ordinary silicate cement solidified body of radioactive waste liquid, enhance the solidification effect of cement solidified body on typical nuclides 90Sr and 137Cs in intermediate-level waste liquid generated by spent fuel reprocessing plants, and realize the efficient solidification of ordinary silicate cement on intermediate- and low-level waste liquid containing radioactive nuclides Cs and Sr. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0020] Figure 1 The present invention provides a flow chart of a method for solidifying a low-level and medium-level waste liquid cement solidification formula containing strontium and cesium according to an embodiment of the present invention. DETAILED DESCRIPTION

[0021] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present invention. It should be noted that the following detailed description is illustrative and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by ordinary technicians in the technical field to which the present invention belongs.

[0022] A formula for preparing low- to medium-level radioactive liquid waste cement solidification suitable for radioactive nuclides 90Sr and 137Cs comprises composite silicate cement, waste liquid, graphene oxide and additives, wherein the waste liquid, graphene oxide and additives account for 45-65%, 0.03-0.07% and 0.12%-0.42% of the cement mass respectively; and the liquid-to-cement ratio is 0.55-0.65.

[0023] The preparation method mainly comprises the following steps:

[0024] (1) Add 6.334 g of cesium chloride and 9.046 g of strontium chloride into 5 L of deionized water to prepare a solution containing Cs + and Sr 2+ Wastewater, including Cs + and Sr 2+ The element concentrations were all 1 g / L;

[0025] (2) weighing cement, graphene oxide solid, additives and the waste liquid obtained in step (1) according to a proportion;

[0026] (3) mixing the graphene oxide solid, the additive and part of the waste liquid to prepare a graphene oxide suspension with a concentration of 5 mg / ml and placing it in an ultrasonic machine for water bath ultrasonication for 10 minutes to obtain a graphene oxide dispersion;

[0027] (4) placing the remaining waste liquid, cement and the graphene oxide dispersion obtained in step (3) into a stirring pot, first stirring slowly for 2 minutes, then stirring rapidly for 10 minutes to stir evenly;

[0028] (5) Pour the stirred cement slurry into a fluidity test mold to test the fluidity of the cement slurry;

[0029] (6) Pour the mixed cement into a Φ50×50mm mold and cure it. The curing conditions are temperature T≈20±5℃ and relative humidity RH≥90%.

[0030] Embodiment 1

[0031] 28 parts of polycarboxylate water reducer and 7 parts of graphene oxide were weighed by mass, mixed with 1400 parts of waste liquid, and dispersed in an ultrasonic cleaning machine in a water bath at room temperature for 10 minutes. The mixture, 10000 parts of composite silicate cement and 5100 parts of waste liquid were placed in a stirring pot and stirred slowly for 2 minutes, then stirred rapidly for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0032] Embodiment 2

[0033] 42 parts of lignin sulfonate water reducer and 7 parts of graphene oxide were weighed by mass, mixed with 1400 parts of waste liquid, and dispersed in an ultrasonic cleaner in a water bath at room temperature for 10 minutes. The mixture, 10,000 parts of composite silicate cement and 5100 parts of waste liquid were placed in a stirring pot and stirred slowly for 2 minutes, then stirred rapidly for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0034] Embodiment 3

[0035] 4 parts of polycarboxylate water reducer and 1 part of graphene oxide were weighed by mass, mixed with 200 parts of waste liquid, and dispersed in an ultrasonic cleaning machine in a water bath at room temperature for 10 minutes. The mixture, 2000 parts of composite silicate cement and 900 parts of waste liquid were placed in a stirring pot and stirred slowly for 2 minutes, then stirred rapidly for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0036] Embodiment 4

[0037] 6 parts of lignin sulfonate water reducer and 1 part of graphene oxide were weighed by mass, mixed with 200 parts of waste liquid, and dispersed in an ultrasonic cleaner in a water bath at room temperature for 10 minutes. The above mixture, 2000 parts of composite silicate cement and 900 parts of waste liquid were placed in a stirring pot and slowly stirred for 2 minutes, then quickly stirred for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0038] Embodiment 5

[0039] 28 parts of polycarboxylate water reducer and 7 parts of graphene oxide were weighed by mass, mixed with 1400 parts of waste liquid, and dispersed in an ultrasonic cleaner in a water bath at room temperature for 10 minutes. The mixture, 10,000 parts of composite silicate cement and 3100 parts of waste liquid were placed in a stirring pot and stirred slowly for 2 minutes, then stirred rapidly for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0040] Embodiment 6

[0041] 42 parts of lignin sulfonate water reducer and 7 parts of graphene oxide were weighed by mass, mixed with 1400 parts of waste liquid, and dispersed in an ultrasonic cleaner in a water bath at room temperature for 10 minutes. The mixture, 10,000 parts of composite silicate cement and 3100 parts of waste liquid were placed in a stirring pot and stirred slowly for 2 minutes, then stirred rapidly for 10 minutes, and then moved to a Φ50×50mm mold, and the test mold was placed under standard conditions for curing. The curing temperature was 20±2°C and the relative humidity was ≥90% to prepare a solidified body.

[0042] Embodiment 7

[0043] The formulations of cement solidification waste liquid containing graphene oxide in Examples 1 to 6 were respectively tested in the laboratory to verify whether the performance of the solidified body meets the construction requirements. The test items and results are as follows:

[0044] 1. Compressive strength: The compressive strength of the waste liquid cement solidified body sample should not be less than 7MPa. The cement solidified bodies in Examples 1 to 6 were tested for compressive strength, and the results showed that the 28d compressive strength was greater than 8MPa.

[0045] 2. Impact resistance: After the waste liquid cement solidified body sample was cured for 28 days, it was dropped freely from a height of 9m onto the concrete floor. The solidified body should not be obviously broken. The cement solidified bodies in Examples 1 to 6 were subjected to impact resistance tests. The results showed that the solidified bodies had good integrity and were not broken.

[0046] 3. Freeze-thaw resistance: After the waste liquid cement solidified body sample was cured for 28 days and subjected to 5 freeze-thaw cycle tests, there should be no obvious cracks or cracks on the appearance, and the loss of compressive strength should not exceed 25%. The cement solidified bodies in Examples 1 to 6 were subjected to freeze-thaw cycle tests, and the results showed that there were no obvious cracks on the appearance of the solidified bodies, and the loss of compressive strength was small, with the maximum loss not exceeding 7%.

[0047] 4. Anti-leaching property: After curing for 28 days, the solidified cement containing waste liquid is immersed in the leaching agent and the leaching liquid is collected. + , Sr 2+ The leaching rate limits for the 42nd day are 4×10 -3 cm / d, 1×10 -3 cm / d, and the cumulative leaching fraction limit values ​​on the 42nd day were 0.26 cm and 0.17 cm respectively. The cement solidified bodies in Examples 1 to 6 were subjected to leaching experiments. When the leaching temperature was 25±2°C and the leaching solution was deionized water, the radionuclide Cs in the wastewater was + , Sr 2+ The leaching rate and cumulative leaching fraction on the 42nd day both met the construction requirements.

[0048] It is shown that the mechanical properties and durability of the cement solidified body obtained by the above formula after 28 days of curing meet the various requirements of construction. The compressive strength of the solidified body is greater than 7MPa. After impact, freeze-thaw, immersion and other tests, the solidified body has good integrity, no cracks on the surface, and little strength loss. + , Sr 2+ The 42d leaching rate and cumulative leaching fraction are lower than the limit requirements in the standard, with good solidification effect and safety, which proves that the addition of graphene oxide can improve the compressive strength of the solidified body and is beneficial to reduce the migration rate of radionuclides in the waste liquid from the pore solution to the outer surface of the solidified body.

[0049] The above is a detailed introduction to the cement solidification formula and solidification method for low-level and medium-level waste liquid containing strontium and cesium provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only applicable to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A cement solidification formula for medium and low-level waste liquid containing strontium and cesium, characterized in that: The invention comprises composite silicate cement, waste liquid, graphene oxide and additives, wherein the waste liquid, graphene oxide and additives account for 45-65%, 0.03-0.07% and 0.12%-0.42% of the cement mass respectively; and the liquid-cement ratio is 0.55-0.

65.

2. The cement solidification formula for medium and low-level waste liquid containing strontium and cesium according to claim 1, characterized in that: The composite silicate cement model is P.C42.5R, the graphene oxide is a high-purity single-layer graphene oxide solid, the additive is a polycarboxylic acid water reducer or a lignin sulfonate water reducer, and the effective ingredient content of the additive is ≥60%.

3. The cement solidification formula for medium and low-level waste liquid containing strontium and cesium according to claim 2, characterized in that: The four components of composite silicate cement, waste liquid, graphene oxide and polycarboxylic acid water reducer account for 60.48%, 39.31%, 0.04% and 0.16% of the cement mass respectively, and the liquid-cement ratio is 0.

65.

4. The cement solidification formula for medium and low-level waste liquid containing strontium and cesium according to claim 2, characterized in that: The mass percentages of composite silicate cement, waste liquid, graphene oxide and lignin sulfonate water reducer are 60.43%, 39.28%, 0.04% and 0.25% respectively, and the liquid-cement ratio is 0.

65.

5. The cement solidification formula for medium and low-level waste liquid containing strontium and cesium according to claim 2, characterized in that: The mass percentages of composite silicate cement, waste liquid, graphene oxide and polycarboxylate water reducer are 64.41%, 35.42%, 0.03% and 0.12% respectively, and the liquid-cement ratio is 0.

55.

6. A cement solidification formula for medium and low-level waste liquid containing strontium and cesium according to claim 2, characterized in that: The mass percentages of composite silicate cement, waste liquid, graphene oxide and lignin sulfonate water reducer are 64.37%, 35.40%, 0.03% and 0.19% respectively, and the liquid-cement ratio is 0.

55.

7. A method for curing a cement solidification formula of medium and low-level waste liquid containing strontium and cesium according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1, weighing composite silicate cement, waste liquid, graphene oxide and additives according to a ratio; Step S2, mixing graphene oxide solid, additives and part of the waste liquid to prepare a graphene oxide suspension with a concentration of 5 mg / ml, and preparing a graphene oxide dispersion by a dispersion process; Step S3, putting the remaining waste liquid, composite silicate cement and the graphene oxide dispersion obtained in step S2 into a cement curing barrel, stirring evenly to obtain cement slurry; Step S4: pour cement slurry into the prefabricated mold and cure it.

8. A method for curing a cement solidification formula of low-level and medium-level waste liquid containing strontium and cesium according to claim 7, characterized in that: In step S4, the curing conditions are temperature T≈20±5° C. and relative humidity RH≥90%.